Design, synthesis and biological evaluation of vortioxetine derivatives as new COX-1/2 inhibitors in human monocytes. Issue 23 (1st December 2020) - Talmon, Maria; Chaudhari, Raju D.; Suryavanshi, Hemant; Chowdhury, Nilkanta; Quaregna, Martina; Pin, Arianna; Bagchi, Angshuman; Biswas, Goutam; Fresu, Luigia G.
Graphical abstract: Highlights: The antidepressant vortioxetine is endowed with a mild anti-COX-1/2 inhibition. Most of the alkyl, acyl and sulphonyl derivatives demonstrated a strong anti-oxidant activity. 1-(2-(2, 4-Dimethylphenylsulfanyl)phenyl)-4-(2-fluorobenzyl)piperazine (6 ) was the best antioxidant and COX-1 inhibitor. Cyclopentylmethyl derivative 3 and 2-(trifluoromethyl)benzyl derivative 7 showed a mild COX-1/2 inhibition. According to docking study 1-(2-(2, 4-dimethylphenylsulfanyl)phenyl)-4-tosylpiperazine(11 ) showed specific COX-2 binding. Abstract: In order to identify a suitable alternative to non-steroidal anti-inflammatory drugs (NSAIDs) we aimed to develop derivatives of vortioxetine, a multimodal anti-depressive drug that has been shownpreviously to be endowed withanti-inflammatory activity in human monocytes/macrophages. Vortioxetine (1 ) was synthesized in good yield and different alkyl and aryl derivatives were prepared based on their structural diversity and easy availability. The compounds were tested on human monocytes isolated from healthy donors for theireffect on superoxide anion production and cytokine gene expression, and for COX-1/2 gene expression and activity modulation. Moreover, a docking study was performed to predict the interactions between the synthesized compounds and COX-1 and COX-2. Correlating experimental biological data to the molecular modelling studies, it emerged that among the novel compounds, 6 was endowed of antioxidant and anti-COX-1 activity, vortioxetine and 3 were good antioxidants and mild anti-COX-1/2 inhibitors, while 7 was a good anti-COX-1/2 inhibitor and 11 was more specific versus COX-2.